Assessing the level of greening in a major city: subjective and objective evaluation on the example of the city of Kyiv - Pleshkanovska Alla Mikhailivna (Bulletin of Geography. Socio-Economic Series, 2020)
One of the ways to ensure the sustainable development of settlements is to improve comfort of living in urban areas. The formation of a developed landscaping system is one of the priorities of modern city development and provides an opportunity to realise the main functions of green areas of public use – ecological, historical, cultural, urban and social. Sufficiency or insufficiency of green areas is determined by indicators both objective (the level or area of landscaping per person), and subjective (the feeling of green space and comfort of urban areas). This study addresses both of these aspects. Significant differences in the findings of sociological surveys conducted earlier were also analysed. Residents of the city of Kyiv completed a questionnaire, which evaluated not only the existing greening system of the city, but also the perceived priority directions for its improvement. Four main criteria for assessing the quality of landscaping elements are proposed – environmental friendliness, contact, accessibility and attractiveness.